Flexible Li[Li0.2Ni0.13Co0.13Mn0.54]O2/Carbon Nanotubes/Nanofibrillated Celluloses Composite Electrode for High-Performance Lithium-Ion Battery - Li, Yan; Zhang, Han; Xiao, Zhe; Wang, Renheng (Frontiers in Chemistry, 2019)
Rapidly-growing demand for wearable and flexible devices is boosting the development of flexible lithium ion batteries (LIBs). The exploitation of flexible electrodes with high mechanical properties and superior electrochemical performances has been a key challenge for the rapid practical application of flexible LIBs. Herein, a flexible composite electrode was prepared from the mixed solutions of Li[Li0.2Ni0.13Co0.13Mn0.54]O2 (LLOs), carbon nanotubes(CNTs), and nanofibrillated celluloses (NFCs) via a vacuum filtration method. The resulting LLOs/CNTs/NFCs electrode delivers an initial discharge capacity of 253 mAh g-1 at 0.1 C in the voltage range from 2.0 to 4.6 V, and retains a reversible capacity of 178 mAh g-1 with 83% capacity retention after 100 cycles at 1 C. The LLOs/CNTs/NFCs electrode exhibits excellent flexibility along with repeated bending in the bending test. The LLOs/CNTs/NFCs electrode after bending test remains a discharge capacity of 149 mAh g-1 after 100 cycles at 1 C, and the corresponding capacity retentions is 76%. The excellent electrochemical performance and high flexibility can be ascribed to the framework formed by CNTs with high conductivity and NFCs with good mechanical properties. The results imply that the as-fabricated electrode can be a promising candidate for the flexible LIBs.